2016
DOI: 10.1002/ejic.201600323
|View full text |Cite
|
Sign up to set email alerts
|

Advanced NMR Methods and DFT Calculations on the Regioselective Deprotonation and Functionalization of 1,1′‐Methylenebis(3‐methylimidazole‐2‐thione)

Abstract: Depending on the temperature, the twofold deprotonation of 1,1′‐methylenebis(3‐methylimidazole‐2‐thione) (1) and the subsequent reaction with 2 equiv. of trimethylsilyl chloride (TMSCl) gives two different bis‐TMS‐functionalized isomers, namely, 1,1′‐methylenebis(3‐methyl‐4‐trimethylsilylimidazole‐2‐thione) (2) and 1,1′‐methylenebis(3‐methyl‐5‐trimethylsilylimidazole‐2‐thione) (3). The cyclic dimethylsilyl‐bridged derivative 1,1′‐methylene‐5,5′‐dimethylsilylenebis(3‐methylimidazole‐2‐thione) (4) can also be ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 98 publications
(52 reference statements)
1
5
0
Order By: Relevance
“…The observed bond lengths and angles are unexceptional and compare well to those found in the structures of the parent imidazol‐2‐thione 1 or the C‐functionalized imidazol‐2‐thiones III and VII [15,17,26] . Silyl substitution produces a slight elongation of the endocyclic C=C bonds by <0.6 Å.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The observed bond lengths and angles are unexceptional and compare well to those found in the structures of the parent imidazol‐2‐thione 1 or the C‐functionalized imidazol‐2‐thiones III and VII [15,17,26] . Silyl substitution produces a slight elongation of the endocyclic C=C bonds by <0.6 Å.…”
Section: Resultssupporting
confidence: 70%
“…An alternative approach to silylimidazole-2-thiones has recently been published by Kuzu et al (Scheme 2). [17] In close analogy to Streubel's procedure for the synthesis of P-functionalized 1,3-diorganoimidazole-2-thiones, methylenebis(3-methylimidazole-2-thione) was deprotonated with nBuLi followed by the addition of Me 3 SiCl to give the backbone silylated bridged species VI. The fused tricyclic species VII was obtained analogously with Me 2 SiCl 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The lithium–C4 bond length (2.116(5) Å) is in a range similar to that of the BR 3 adducts 51 . Studies about regioselective backbone deprotonation of methylene-bridged bis­(imidazole-2-thiones) leading to a NHC lithium complexes were also reported . Lithium a NHC complexes have been utilized in the postcoordination backbone functionalization of NHCs …”
Section: Nhc Complexes Of Main Group Elementsmentioning
confidence: 99%
“…Studies about regioselective backbone deprotonation of methylene-bridged bis(imidazole-2-thiones) leading to aNHC lithium complexes were also reported. 135 Lithium aNHC complexes have been utilized in the postcoordination backbone functionalization of NHCs. 136 Lithium NHC complexes with an (anionic) backbonesubstituent have also been reported.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…We have occasionally observed that the solution and solid-state structures of group 1 salts may be different and are strongly dependent on the choice of solvent . Consequently, we have studied the solution structure of 2 via multinuclear NMR spectroscopy together with 1 H and 7 Li PGSE NMR diffusion measurements.…”
Section: Resultsmentioning
confidence: 99%